Experimental investigation of the behaviour of spiral steel fibre reinforced concrete beams subjected to drop-weight impact loads - Hao, Y.; Hao, Hong; Chen, G. (Kluwer Academic Publishers, 2014)
Concrete is a brittle material with much lower strength in tension as compared to that in compression. Adding fibres into concrete mix has been intensively investigated to increase the ductility, the crack control and energy absorption capabilities. A new type of steel fibre with spiral shape has been proposed recently. It has been demonstrated by laboratory tests that the spiral-shaped fibres have larger displacement capacity and provide better bonding into the concrete mix compared to other types of fibres such as hooked-end, deformed and corrugated fibres. The present study carries out drop-weight impact tests to study the structural responses of concrete beams reinforced with different types of steel fibres. Plain concrete and concrete reinforced by the commonly used hooked-end steel fibres and the proposed spiral-shaped steel fibres were tested. Two volume fractions, i.e. 0.5 and 1.0 %, of fibres were used to prepare steel fibre reinforced concrete (SFRC) specimens. Ø100–200 mm cylindrical specimens were also prepared and tested to determine the static properties of the concretes. Centre-point flexural tests were conducted on 100 × 100 × 350 mm beams with span length of 300 mm under drop-weight impact loads.The static tests were carried out using hydraulic testing machine and the impact tests were conducted using an instrumented drop-weight testing system. A 15.2 kg hard steel was used as the drop-weight impactor. Two drop heights, namely 0.5 and 1.0 m, were adopted in performing the repeated impact tests. The high-speed camera, fast-response load cells and laser linear variable differential transformers were used to record the failure processes, forces and displacements of the tested specimens under impact loads. The force–displacement relations and the corresponding energy absorption capabilities of the SFRC beams were obtained, compared and discussed. The advantage and effectiveness of the spiral-shaped steel fibres in increasing the performance of SFRC beam elements under impact loads are examined.